Overview of NCDs among Muslims - Abdul Rahman, Abdul Rashid (International Journal of Human and Health Sciences (IJHHS), 2024)
Non-Communicable Diseases (NCDs) have emerged as the leading cause of global mortality and morbidity in recent years, accounting for 7 out of every 10 deaths worldwide. Ischemic Heart Diseases (IHD) and cerebrovascular accidents (CVA) are the top two killers, claiming 9 million and 6 million lives in 2019, respectively. However, in low-income countries, neonatal mortality and lower respiratory tract infections surpass IHD and CVA, although the latter two are rapidly rising. In all other economies, including lower-middle-income, upper-middle-income, and high-income countries, IHD and CVA are the primary causes of death. This prevalence of NCDs, particularly IHD and CVA, is a major concern in Muslim-majority countries, most of which belong to low or middleincome categories. Alarmingly, these conditions are affecting people at younger ages, which will have a significant socio-economic impact. The rise in NCDs, particularly IHD and CVA, is strongly linked to risk factors such as hypertension, smoking, diabetes, and hyperlipidemia, often referred to as the "big four." Smoking rates have decreased, but diabetes is surging, with three Muslim countries (Pakistan, Kuwait, and Egypt) in the top 10 globally. Hypertension, a major risk factor for CVD, has the highest prevalence in Iraq, Brunei Darussalam, and Afghanistan among Muslim nations. Malaysian men have the highest prevalence of elevated non-HDL cholesterol, and their women are second globally. Lebanon and Brunei also have high rates. Furthermore, the detection, treatment, and control rates of these risk factors in Muslim countries are concerning. Malaysia's integrated approach has demonstrated that improving these rates can reduce cardiovascular mortality, as suboptimal treatment contributes to 84% of such deaths. To combat the NCD epidemic, Muslim nations must unite their efforts. Early preventive lifestyle modifications should be encouraged, drawing from Islamic teachings. Integrated strategic action plans need formulation and systematic implementation, especially in countries lacking such plans, to curb this growing health crisis. International Journal of Human and Health Sciences Supplementary Issue 01: 2024 Page: S5